PENGARUH PEMBERIAN CHLORELLA SP. DENGAN KEPADATAN BERBEDA TERHADAP PERTAMBAHAN POPULASI Moina sp. - Suprayitno Hamdan; Rosyadi; T. Iskandar Johan; Khairul Hadi (DINAMIKA PERTANIAN, 2024)
Chlorella sp. is a type of phytoplankton that shows promise as a feed source for Moina sp. due to its appropriate size, comprehensive nutritional profile, and ease of cultivation. The goal of this research is to evaluate the impact of various densities of Chlorella sp. on the population growth of Moina sp. This study employed an experimental approach using a Completely Randomized Design (CRD) with four treatments and three replicates. The treatments consisted of P1 = Chlorella at a density of 75 × 10^4 cells/mL, P2 = 100 × 10^4 cells/mL, P3 = 125 × 10^4 cells/mL, and P4 = 150 × 10^4 cells/mL. The parameters monitored included population growth, growth rate, and water quality factors such as temperature, pH, dissolved oxygen (DO), and ammonia (NH3) levels. The findings indicated that the highest population of Moina sp. occurred with the application of Chlorella sp. at a density of 150 × 10^4 cells/mL, reaching 8,258 individuals per liter on the 14th day. In contrast, the lowest population was associated with the density of 75 × 10^4 cells/mL, which resulted in 1,958 individuals per liter on the 12th day. The results suggest that varying the densities of Chlorella sp. had a highly significant effect (p < 0.05) on the population growth of Moina sp